Acesso à justiça no direito processual civil brasileiro - Cunha Filho, José Sebastião Fagundes (2008)
The present dissertation has the objective of examining the access to justice in the Brazilian civil case haw and therefore, extends for two chapters. The first deals with the fundamental institutes for the comprehension of access to justice. The study begins with the conception of the state and it s relation with politic and after with law. Afterwards philosophical theories are exposed about the concept of justices throughout history. So, a proposal of access to justice is created as access to fair juridical to order with the receiving of justice. The second chapter begins with the examination of juridical case concepts and of case law. The matters that involve juridical case relationship are analysed, under the focus the correct legal process, presenting some other constitutional principles that relate with it, such as, the contrary principle, the free motivating convincement, the agreement or the reduction and, finally, the study of the elements of action: parts, cause of ordering and order, and as they link the justice activity always with en phases on the effectiveness of justice guard under it s characteristic of making of the entity responsible for pacifying of social conflicts